PERAN PEMIMPIN DALAM MENINGKATKAN KOMITMEN ORGANISASIONAL DI PT. LSS (LEMBAH SAWIT SUBUR) KECAMATAN LINGGANG BINGUNG KABUPATEN KUTAI BARAT KALIMANTAN TIMUR - Dede Leonardo (ADMINISTRASI PUBLIK, 2020)
Dede Leonardo, "The Role of Leaders in Increasing Organizational Commitment in PT. LSS (Lembah Sawit Subur), Linggang Bingung District, West Kutai Regency, East Kalimantan "Human resources are a very important factor in an organization both large and small scale organizations. In large-scale organizations, human resources are seen as a very decisive element in the business development process, the role of human resources is becoming increasingly important. The development of government will be realized if it is supported by a qualified state apparatus.In public organizations, subordinates work always depends on the leader. If the leader does not have the ability to lead, then very complex tasks cannot be done well. If managers are able to carry out their functions properly, it is very likely that the organization can achieve its goals. An organization needs effective leaders, who have the ability to influence the behavior of their members or subordinates. So, a leader or head of an organization will be recognized as a leader if he can exert influence and be able to direct his subordinates towards the goals of the organization.Nearly most of the definitions of leadership have a common point of the keyword "a process of influence". But we find that the conceptualization of leadership is different in many ways. The difference in "who uses the influence, the purpose of the effort to influence, how to use that influence".Stephen P. Robbins (Badeni, 2014) argues, leadership as the ability to influence a group toward the achievement of goals that leadership can be defined as the ability of someone to influence a group towards the achievement of goals.The leadership elements according to Stogdill are:• The involvement of organizational members as followers• Distribution of power between leaders and members of the organization• Legitimacy is given to followers• Leaders influence followers in a variety of ways.Leadership is an activity to influence the behavior of others so that they want to be directed to achieve certain goals. Leadership is defined as the ability to move or motivate a number of people to simultaneously do the same activities and aim at achieving their goals. Leadership is also a process of moving a group or groups in the same direction without coercion.